Efficacy of Guava Leaf Decoction in Lowering Blood Glucose in Diabetes Mellitus: A Systematic Review - Naurah, Ghina Nurjihan; Oktaviani, Sophia; Rosalina, Dela Gita; Gandara, Purnama; Setiawan, Henri; Waluyo , Endrian Mulyadi Justisiya (Genius Journal, 2025)
Introduction: Diabetes mellitus is a chronic metabolic disorder characterized by elevated blood glucose levels due to insulin resistance or insufficient insulin secretion. The rising global prevalence of DM has led to increased interest in alternative therapies, including herbal remedies such as guava leaf decoction, which is believed to possess hypoglycemic properties. Objective: This systematic review aims to evaluate the efficacy of guava leaf decoction in reducing blood glucose levels in patients with diabetes mellitus. Methods: A comprehensive literature search was conducted across four databases—PubMed, ProQuest, Garuda, and JSTOR—for studies published between 2020 and 2024. Inclusion criteria were studies involving diabetic patients receiving guava leaf decoction as an intervention, with outcomes measured in terms of blood glucose levels using glucometers. The selection and quality appraisal of studies were independently performed by two to three reviewers, following the PRISMA guidelines. The CASP checklist was used for methodological quality assessment. Extracted data included study authors, intervention details, facilitators, setting, session frequency, duration, and delivery method. Results: Eight eligible studies comprising a total of 229 participants were included. The findings consistently demonstrated that guava leaf decoction significantly reduced blood glucose levels. Effective regimens included twice-daily administration for 7 days or once daily (250 ml) for 14 days. Benefits were observed in both diabetic and obese individuals. Conclusion: Guava leaf decoction shows potential as a complementary therapy in the management of diabetes mellitus by naturally lowering blood glucose levels. Further clinical trials are recommended to confirm its efficacy and safety.